Equity Policies in Global Higher Education Reducing Inequality and Increasing Participation and Attainment - Tavares, Orlanda; Sá, Carla; Sin, Cristina; Amaral, Alberto (Issues in Higher Education, 2022)
This book discusses and analyses global policies and practices aimed at promoting equity in higher education participation and attainment. Although the massification of higher education systems has facilitated the participation of students from deprived backgrounds, socioeconomic inequalities persist in access to the most prestigious institutions and programmes. Privileged students benefit from a number of advantages in the competition for selective and scarce places: access to information, lower aversion to debt, higher expectations, better previous schooling and higher academic achievement. The chapters present a critical analysis of equity policies in different countries - with or without affirmative action policies, within a context of neoliberal policies or within a social democratic model - and the reasons why they have failed to promote equity and fairness, preventing students from achieving their full educational potential. This is an open access book.